They knew they were Pilgrims : Plymouth Colony and the contest for American liberty - Turner, John G. (Yale University Press, 2020)
In 1620, separatists from the Church of England set sail across the Atlantic aboard the Mayflower. Understanding themselves as spiritual pilgrims, they left to preserve their liberty to worship God in accordance with their understanding of the Bible. There exists, however, an alternative, more dispiriting version of their story. In it, the Pilgrims are religious zealots who persecuted dissenters and decimated the Native peoples through warfare and by stealing their land. The Pilgrims' definition of liberty was, in practice, very narrow. Drawing on original research using underutilized sources, John G. Turner moves beyond these familiar narratives in his sweeping and authoritative new history of Plymouth Colony. Instead of depicting the Pilgrims as otherworldly saints or extraordinary sinners, he tells how a variety of English settlers and Native peoples engaged in a contest for the meaning of American liberty. From dust jacket